2022
DOI: 10.1177/15280837221106232
|View full text |Cite
|
Sign up to set email alerts
|

Modified stress field model for critical tearing strength of architectural coated fabrics

Abstract: This report presents a new critical tearing strength prediction model, the modified stress field model. Firstly, the critical tearing strength of six coated fabrics is obtained using the single-edge notched tests. The results show that the warp and weft strength utilization of different coated fabrics is similar. Based on the test data, the prediction effects, parameter meanings, and basic properties of three models, namely Thiele’s empirical formula, the stress field model, and the modified stress field model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Performed investigations of the coated woven fabrics have shown that the mechanical parameters are highly influenced by temperature changes [13][14][15]; changes in behaviour under uniaxial, biaxial and creep loadings [16][17][18][19][20][21]; glass threads based and PTFE-coated woven fabrics occur a reduction in the tensile strength resulting under waterlogged [22,23]; prove degradation of the tensile strength exposed to weathering and ageing impacts and cyclic loading [24][25][26][27]; exhibits highly material nonlinearity with identified viscoelastic, viscoplastic behaviour [28][29][30][31][32][33][34]; puncture resistance strength increases with the increase of weight percentage of fibres and initial notch significantly reduce the ultimate strength [35][36][37][38]; the failure strength depends on the stress ratio and off-axial angle [39][40][41][42]. The investigations are also performed on: tearing behaviours and tearing strength propagation mechanisms [41,[43][44][45][46], off-axis tearing properties [47,48], achieving 3D strain surfaces on coated woven fabrics, and refined biaxial test procedures [49,50], modelling multi-scale progressive damage to investigate the damage and failure behaviours…”
Section: Introductionmentioning
confidence: 99%
“…Performed investigations of the coated woven fabrics have shown that the mechanical parameters are highly influenced by temperature changes [13][14][15]; changes in behaviour under uniaxial, biaxial and creep loadings [16][17][18][19][20][21]; glass threads based and PTFE-coated woven fabrics occur a reduction in the tensile strength resulting under waterlogged [22,23]; prove degradation of the tensile strength exposed to weathering and ageing impacts and cyclic loading [24][25][26][27]; exhibits highly material nonlinearity with identified viscoelastic, viscoplastic behaviour [28][29][30][31][32][33][34]; puncture resistance strength increases with the increase of weight percentage of fibres and initial notch significantly reduce the ultimate strength [35][36][37][38]; the failure strength depends on the stress ratio and off-axial angle [39][40][41][42]. The investigations are also performed on: tearing behaviours and tearing strength propagation mechanisms [41,[43][44][45][46], off-axis tearing properties [47,48], achieving 3D strain surfaces on coated woven fabrics, and refined biaxial test procedures [49,50], modelling multi-scale progressive damage to investigate the damage and failure behaviours…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the puncture resistance of the coated fabric was closely related to the size of the punch. Zhang et al 28 investigated the tearing performance of PVC-coated fabrics and proposed a new model to predict the critical tear strength. The results showed that the strength utilization of warp and weft yarns of different coated fabrics was similar.…”
Section: Introductionmentioning
confidence: 99%
“…Strong dimensional stability and good cover are seen between them by woven fabric. Strength is one of the most significant features of woven fabric [8]. In stretching a test piece to a breaking point, the highest tensile force measured is called tensile strength or breaking strength.…”
Section: Introductionmentioning
confidence: 99%